2010
DOI: 10.1002/ijc.25150
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness analysis of cervical cancer prevention based on a rapid human papillomavirus screening test in a high‐risk region of China

Abstract: This study assessed the cost-effectiveness of a new, rapid human papillomavirus (HPV)-DNA screening test for cervical cancer prevention in the high-risk region of Shanxi, China. Using micro-costing methods, we estimated the resources needed to implement preventive strategies using cervical cytology or HPV-DNA testing, including the Hybrid Capture 2 (hc2) test (QIAGEN Corp., Gaithersburg, MD) and the rapid HPV-DNA careHPV TM test (QIAGEN). Data were used in a previously published model and empirically calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 24 publications
3
68
1
Order By: Relevance
“…In Sweden, Bisoleti et al showed that combined HPV DNA testing and cervical cytology three times per life time starting at age 32 was the most cost effective method (Bistoletti et al, 2008). Levin suggested rapid HPV DNA testing three times in a lifetime and starting at age 35 was the most cost-effective strategy at the national, township and county level in China (Levin et al, 2010).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 4 more Smart Citations
“…In Sweden, Bisoleti et al showed that combined HPV DNA testing and cervical cytology three times per life time starting at age 32 was the most cost effective method (Bistoletti et al, 2008). Levin suggested rapid HPV DNA testing three times in a lifetime and starting at age 35 was the most cost-effective strategy at the national, township and county level in China (Levin et al, 2010).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
“…Four articles in four high income countries (Goldie et al, 2001;2004;Mandelblatt et al, 2002a;Bistoletti et al, 2008;Burger et al, 2012;de Kok et al, 2012), nine middle income countries from seven articles Andres-Gamboa et al, 2008;Vijayaraghavan et al, 2009;Chow et al, 2010;Levin et al, 2010) and 1 article in low income countries suggested starting age after age 30 (Table 1).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 3 more Smart Citations